2010
DOI: 10.1002/bdra.20685
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic disruption: The effects of early developmental exposures

Abstract: Through DNA methylation, histone modifications, and small regulatory RNAs the epigenome systematically controls gene expression during development--both in utero and throughout life. The epigenome is also a very reactionary system; its labile nature allows it to sense and respond to environmental perturbations to ensure survival during fetal growth. This pliability can lead to aberrant epigenetic modifications that persist into later life and induce numerous disease states. Endocrine disrupting compounds (EDCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(137 citation statements)
references
References 68 publications
3
128
0
3
Order By: Relevance
“…The metastable epiallele, CDK5-activator binding protein (Cabp IAP ) has been widely used as a biomarker of environmental exposure alteration to the epigenome. [27][28][29][30] Until now, the longitudinal changes in Cabp IAP DNA methylation level had not been described. The Cabp IAP locus has a high baseline level of methylation, explaining the small average increase across exposure groups (1.27%).…”
Section: Discussionmentioning
confidence: 99%
“…The metastable epiallele, CDK5-activator binding protein (Cabp IAP ) has been widely used as a biomarker of environmental exposure alteration to the epigenome. [27][28][29][30] Until now, the longitudinal changes in Cabp IAP DNA methylation level had not been described. The Cabp IAP locus has a high baseline level of methylation, explaining the small average increase across exposure groups (1.27%).…”
Section: Discussionmentioning
confidence: 99%
“…Although the relative proportions of nonshared (intrauterine) environment versus stochastic influences on the neonatal epigenome remain to be demonstrated, Feinberg and colleagues have proposed a model in which a genetically inherited propensity to stochastic variability in DNA methylation has evolved to increase fitness in a varying environment (Feinberg and Irizarry 2011). Furthermore, a combination of influences have been proposed to explain the phenomenon of metastable epialleles, which are variably expressed due to epigenetic modifications that are established in a stochastic manner during early development, and that are also environmentally labile (for review, see Bernal and Jirtle 2010).…”
Section: What Function Does Variable Methylation Serve?mentioning
confidence: 99%
“…8 Many types of environmental challenges imposed on the parent, such as hunger, specific diets, toxins, or trauma have been found to influence the development of the offspring. 3,[9][10][11][12] Whereas some studies examined the phenotype of immediate offspring, others observed changes in several subsequent generations. The transmission of phenotypic changes to grandchildren (F3 generation) and following generations is also termed 'transgenerational inheritance' and assumes that the inducing agent has not been in direct contact with the offspring, whereas an effect on the immediately succeeding generation may be termed 'intergenerational inheritance'.…”
Section: Introductionmentioning
confidence: 99%